2020
DOI: 10.3390/vetsci7040183
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Findings in Bitches Affected by Closed Cervix Pyometra

Abstract: Pyometra is considered the most common disease in intact bitches, being associated with potentially life-threatening disorders. Myocardial damage is a potentially life-threatening consequence of pyometra. The aim of this study was to describe the electrocardiographic patterns in bitches affected by closed cervix pyometra, to assess the clinical relevance of electrocardiographic changes with the occurrence of pyometra, and to relate their severity with laboratory and clinical findings. A total of 39 bitches wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(67 reference statements)
1
4
1
Order By: Relevance
“…The maximum average activity of ALT immediately before the surgery in the control group was 46 u/L, and in the diseased animals 3.9‐fold higher (180 u/L). Similar results have been published by Pugliese et al (2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The maximum average activity of ALT immediately before the surgery in the control group was 46 u/L, and in the diseased animals 3.9‐fold higher (180 u/L). Similar results have been published by Pugliese et al (2020).…”
Section: Discussionsupporting
confidence: 93%
“…The p value for the difference between the average ALP activities at 0 h and 12 h was p < .01, and p < .05 at all the other time points. Increased ALP activity, and serum bilirubin and cholesterol concentrations may suggest intrahepatic cholestasis, which is also considered to be a result of endotoxemia (Pugliese et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Certain research about the subject approached in this study showed the involvement of cardiac abnormalities such as sinus tachycardia, ventricular premature complexes, increased amplitude of T wave, and ST depression (Pugliese et al 2020). However, our study does not specify any significant involvement of myocardial damage.…”
Section: Discussioncontrasting
confidence: 52%
“…Historically, poor attention has been paid by veterinary cardiologists to an important component of ventricular repolarisation, namely the ST segment, whose interpretation is currently performed almost empirically in small animal practice. This knowledge gap can have relevant clinical consequences, as it may not allow for the early identification of ventricular repolarisation abnormalities expressed in the form of ST segment changes that may arise from myocardial injury due to cardiac (Tilley 1992b, Davainis et al 2004, Sleeper et al 2015, Santilli et al 2018b, Lekane et al 2020) and extracardiac diseases (Tilley 1992b, Dvir et al 2004, Surachetpong et al 2016, Santilli et al 2018b, Pugliese et al 2020, the administration of drugs and medium contrast agents (Tilley 1992b, Khurana et al 2014, Santilli et al 2018b, Tamogi et al 2020) and electrolyte abnormalities (Tilley 1992b, Santilli et al 2018b.…”
Section: Introductionmentioning
confidence: 99%
“…2018b , Pugliese et al . 2020 ), the administration of drugs and medium contrast agents (Tilley 1992b , Khurana et al . 2014 , Santilli et al .…”
Section: Introductionmentioning
confidence: 99%